Argumentacja legitymizująca przynależność Ziem Zachodnich i Północnych do Polski w pierwszych latach po II wojnie światowej = The early post-war propaganda of the Western and Northem Territories thes to Poland - Mazur, Mariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper's main focus is an analysis of the propaganda arguments used over the period of 1944-1948 to legitimise Poland's acquisition of the Western and Northem Terrirories. The approach adopted is a systematic one. Most commonly, legitimisation is viewed as the interaction between the authorities and the society.
Keywords: Ziemie Zachodnie i Północne; Polska - historia - od 1944 r.; propaganda komunistyczna